1995
DOI: 10.1113/jphysiol.1995.sp020845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ca2+ channel blockers on transmitter release and presynaptic currents at the frog neuromuscular junction.

Abstract: 1. The effects of the calcium channel blockers, funnel‐web spider toxin (FTX), omega‐agatoxin IVA (omega‐Aga IVA) and omega‐conotoxin GVIA (omega‐CgTX), were tested on transmitter release and presynaptic currents in frog motor nerve endings. 2. Evoked transmitter release was blocked by FTX (IC50 = 0.02 microliter ml‐1) and omega‐CgTX (1 microM) but was not affected by omega‐Aga IVA (0.5 microM). When FTX (0.1 microliter ml‐1) was assayed on spontaneous release either in normal Ringer solution or in low Ca(2+)‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 45 publications
4
47
0
Order By: Relevance
“…This is consistent with findings at mature frog neuromuscular junctions, at which it has been shown that -CgTX blocks all evoked transmitter release (Kerr and Yoshikami, 1984;Koyano et al, 1987;Katz et al, 1995) and some spontaneous release (Grinnell and Pawson, 1989). In the present study, nimodipine blocked ϳ17% of I Ca , suggesting the presence of L-type Ca channels as well.…”
Section: Types Of Ca Channels and Their Coupling To Transmitter Releasesupporting
confidence: 80%
“…This is consistent with findings at mature frog neuromuscular junctions, at which it has been shown that -CgTX blocks all evoked transmitter release (Kerr and Yoshikami, 1984;Koyano et al, 1987;Katz et al, 1995) and some spontaneous release (Grinnell and Pawson, 1989). In the present study, nimodipine blocked ϳ17% of I Ca , suggesting the presence of L-type Ca channels as well.…”
Section: Types Of Ca Channels and Their Coupling To Transmitter Releasesupporting
confidence: 80%
“…In frog and lizard neuromuscular synapses, N-or L-type channels mediate transmission (Lindgren and Moore, 1989;Katz et al, 1995;Arenson and Gill, 1996).…”
Section: Different Ca 2؉ Channel Types Are Differentially Colocalizedmentioning
confidence: 99%
“…The BK channel is an attractive candidate. In virtually all synapses examined, the BK channel is a prominent K ϩ channel at presynaptic nerve endings (Anderson et al, 1988;Farley and Rudy, 1988;Lindgren and Moore, 1989;Tabti et al, 1989;Morita and Barrett, 1990;Sivaramakrishnan et al, 1991;Robitaille et al, 1993;Wangemann and Takeuchi, 1993;Katz et al, 1995;Vatanpour and Harvey, 1995;Knaus et al, 1996;Sun et al, 1999;Zhou et al, 1999;Yazejian et al, 2000;Misonou et al, 2006), where it colocalizes with voltage-gated Ca 2ϩ channels (Robitaille et al, 1993;Issa and Hudspeth, 1994;Yazejian et al, 1997;Yazejian et al, 2000), and may serve as an important negative regulator of neurotransmitter release (Robitaille et al, 1993;Wang et al, 2001;Raffaelli et al, 2004). Several lines of evidence suggest that BK channel activity may be modulated by CaMKII: (1) BK channels reconstituted into artificial lipid bilayers are activated by ATP, which is blocked by a CaMKII inhibitor (Muller et al, 1996); (2) interactions between 14-3-3 and Slob, which are proteins that control Drosophila BK channel activity, may be modulated by CaMKII (Zhou et al, 1999); and (3) BK channels contribute to afterhyperpolarization of mouse vestibular nucleus neurons in a CaMKII-dependent manner (Nelson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%